POTENSI PENYU HIJAU (Chelonia mydas L.) SEBAGAI STRATEGI PENGEMBANGAN WISATA EDUKASI DI KAWASAN PANTAI PANGUMBAHAN UJUNG GENTENG SUKABUMI JAWA BARAT - Leonita, Geneis Dietri; Satjapradja, Ombo; Meiganati, Kustin Bintani (Universitas Nusa Bangsa, 2018)
Pangumbahan beach is one of the areas that has the potential of diverse resources ranging from tourism, agriculture, forestry and especially marine resources and fisheries one green turtle. Pangumbahan into turtle nesting areas and potentially Education tourist, but turtle selling still occurs illegally. For this purpose, this study aims to examine the Green Turtle potential including laying, incubation, and turtle hatching, to find out the visitor's interest in Green Turtle, and to plan the development of Green Turtle-based Education Tourist program to Green Turtle conservation manager. The research method used quantitative and qualitative methods of SWOT analysis with field observation, interview with purposive sampling, and questionnaire. The results showed that in the Pangumbahan Coast Region yielded IFAS 0.64 and EFAS 0.60 from the results then the location of the strategy is in quadrant I.